THE STRENGTH AND LOSSES OF NADIR SHAH’S ARMY IN THE DAGESTAN CAMPAIGN OF 1741-1743 - Musaev, Mahac Abdulaevic (History, Archeology and Ethnography of the Caucasus, 2022)
A number of solid monographs are dedicated to Nadir Shah’s campaign in Dagestan in 1741-1743. While reviewing these studies, one can note a significant discrepancy in the estimations of the size of Nadir Shah’s troops during the invasion of Dagestan in the spring of 1741. The authors provide information that specifies the army’s size ranging from “several dozen” to “one hundred and fifty thousand” men. However, they mainly cite a very limited range of sources of information provided by P.G. Butkov and L. Bazin. Meanwhile, the Foreign Policy Archives of the Russian Empire stores encrypted reports of the Russian residents at Nadir Shah’s court Ivan Kalushkin and Vasily Bratishchev. Examination of their information provides an idea ofthe number of troops of the Shah’s army in the war, as well as determine the number of losses of his troops: the grand total of soldiers in the Dagestan campaign reached approximately 110 thousand people. Along with the army, there were about 40,000 service personnel and women. Of the soldiers, more than 82 thousand died in Dagestan and a small number of injured men were sent home. Most of the losses were due to combat, less – to hunger and diseases. The losses among the service personnel might have been just as large. The reports of the Russian residents at the Persian court are a very informative source, from which we can learn many interesting details not only about the number of troops, losses, but also the chronology of military events, the results of battles, about Nadir Shah’s tactics and strategy, about the problems of the military campaign, their solutions, international relations and lots of other historical information.